Depressão e distúrbios do sono em professores - Vian, Bianca (2022)
The teaching profession is marked by several demands that increase the overload in physical terms and, above all, mental health. Among the manifestations of illness resulting from mental exhaustion, stand out depressive disorders and the possible association with sleep disorders. Thus, discussing the profession and the mental health of teachers contributes to draw attention to the importance of strengthening educational policies that value the complexity involved in the profession. Therefore, the objective of this dissertation is to analyze the prevalence of depression and its association with sleep quality in teachers. This is a cross-sectional, exploratory descriptive study, with a quantitative approach, which was part of a larger project entitled Gerontological education as a strategy to promote multigenerational interaction for healthy living and aging, which is part of the research line biopsychosocial aspects of human aging. The sample was composed of 361 teachers, residents of the state of Rio Grande do Sul, who agreed to voluntarily participate in the study by means of an, online questionnaire. The study falls on the variables associated with self-reported depression, the Pittsburgh Sleep Quality Index (PSQI-BR) and the Epworth Scale (ESSBR). In the statistical analysis, to describe the profile of the sample, frequency tables of the categorical variables were made with values of absolute and relative frequencies and descriptive statistics of the numerical variables. The Chi-square test was used to compare the categorical variables. The significance level adopted was 5%. The dissertation’s resulting paper, Auto-referred depression and relation to sleep disturbances in teachers, focuses on the teaching category, women and elementary school teachers, being more susceptible to psychological illness than the general population. The discussions and results obtained so far corroborate in similar fashion to evidences from other studies which point out the depression prevalence and the association to poor sleep quality in teachers.